Analisa Kebutuhan Daya Listrik Terpasang pada Gedung CC Fkip Untirta Lantai 1 sampai 3 - Shafa Yuniar Yasmin; Iqbal Maulana; Hijroh Tamamil Gina; Didik Aribowo (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
In the construction of a building, it is necessary to install a good electrical installation and calculate the required electrical power to be used because this is the initial foundation for building operation so that it can be used by building users. used is still within normal limits or not. The method used by researchers is qualitative with data collection techniques from literature studies and observations. In the findings of the researchers' observations, the results obtained that the electricity demand for the CC FKIP UNTIRTA building is still within normal limits because its use is in accordance with the needs of each room.